2013
DOI: 10.1161/circresaha.111.300502
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-28 Deletion Exacerbates Cardiac Dysfunction and Rupture After Myocardial Infarction in Mice by Inhibiting M2 Macrophage Activation

Abstract: Rationale Matrix metalloproteinase (MMP)-28 regulates the inflammatory and extracellular matrix (ECM) responses in cardiac aging, but the roles of MMP-28 after myocardial infarction (MI) have not been explored. Objective To determine the impact of MMP-28 deletion on post-MI remodeling of the left ventricle (LV) Methods and Results Adult C57BL/6J wild type (WT, n=76) and MMP null (MMP-28−/−, n=86) mice of both sexes were subjected to permanent coronary artery ligation to create MI. MMP-28 expression decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
209
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(221 citation statements)
references
References 56 publications
8
209
2
Order By: Relevance
“…For example, macrophage treatment with LPS (1 g/ml) and interferon-␥ (20 ng/ml) increased Tnf␣ and Ccl3 expression 100-fold, whereas SPARC induced 2-fold increases in these two genes (35). Of note, in addition to SPARC increasing Tnf␣ and Ccl3, SPARC also decreased Mrc1 expression by 62%, whereas IL-4, an M2 driver, induces a 3.5-fold increase (35).…”
Section: Ccl5 (M1)mentioning
confidence: 99%
“…For example, macrophage treatment with LPS (1 g/ml) and interferon-␥ (20 ng/ml) increased Tnf␣ and Ccl3 expression 100-fold, whereas SPARC induced 2-fold increases in these two genes (35). Of note, in addition to SPARC increasing Tnf␣ and Ccl3, SPARC also decreased Mrc1 expression by 62%, whereas IL-4, an M2 driver, induces a 3.5-fold increase (35).…”
Section: Ccl5 (M1)mentioning
confidence: 99%
“…In both chronic conditions and myocardial infarction, inflammatory cytokines induce tissue remodeling and degradation of ECM in the myocardium (Gullestad et al, 2012). The loss of ECM can result in a temporary decrease in the passive wall stiffness and increase in diastolic strains in the infarct region, which increase the chance of myocardial wall rupture (Banerjee et al, 2006;Gao et al, 2005;Ma et al, 2013). Deposition of de novo ECM is necessary to maintain structural integrity and requires the switch from inflammatory to profibrotic signaling factors (Frangogiannis, 2014).…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…Several other MMPs have been reported to have an effect on M polarization (23,33). A recent study showed that Mmp28 gene inactivation impaired M2-M polarization and resulted in an aggravated cardiac dysfunction after myocardial infarction in mice (23).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that Mmp28 gene inactivation impaired M2-M polarization and resulted in an aggravated cardiac dysfunction after myocardial infarction in mice (23). Another study showed that loss of MMP28 reduced M2 polarization and protection from bleomycin-induced fibrosis (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation